Chemical engineering. - Harker, J H.; Backhurst, J R.; Richardson, J.F.; Coulson, J.M. ([S.l.] : Butterworth-Heinemann, 1996)
Coulson and Richardson's classic series provides the student with an account of the fundamentals of chemical engineering and constitutes the definitive work on the subject for academics and practitioners. Each book provides clear explanations of theory and thorough coverage of practical applications, supported by numerous worked examples and problems. Thus, the text is designed for students as well as being comprehensive in coverage. The first volume focuses on the general mechanisms of diffusion, fluid flow and heat transfer. Revised and updated throughout, the fifth edition also includes new material on effectiveness of heat exchangers, and a new section on simultaneous reactions and unsteady state mass transfer. In addition, the text has been reset and all the diagrams redrawn, resulting in a book that is clearer and easier to use than ever before.
Keywords: Chemical engineering